Colonización de prácticas alimentarias de mujeres indígenas migrantes residentes del área metropolitana de Monterrey - Alejandro Román & Jimena Gaspar (Facultad de Trabajo Social y Desarrollo Humano, 2023)
Qualitative study with the aim of knowing the process of colonization of food practices of migrant indigenous women residing in the Monterrey metropolitan area (AMM). It was used the theory of communicative action as theoretical support. It was found that when the participants lived in rural areas they mainly maintained their traditionally indigenous diet, and their food mainly came directly from their harvests, backyards, and local sales. No colonization was observed while living in the rural area. However, when indigenous women migrated to the AMM, their diet changed to a mestizo diet, since it was colonized mainly by living with social agents such as employers, partners, and relatives. It is important to consider the high consumption of industrialized products in indigenous population since this has led to the increase in their prevalence of chronic diseases.